PENERAPAN ICE BREAKING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN RASA PERCAYA DIRI SISWA VIII B SMP BINA HARAPAN BANGSA - Fauzan, Gagan Aditya; Aripin, Usman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The problem of self-confidence is often experienced by students in learning activities. This is due to several factors, it can be from students who tend to be shy, it can also be from the teacher who can not bring students confidence in learning. Therefore, this study aims to determine the level of confidence in Bina Harapan Bangsa Middle School students with indicators of self-confidence that are used are students who have sufficient intelligence, have social skills, and are able to overcome various emerging tensions. With the initial problem, the solution is to apply Ice Breaking to learning. This research was conducted on students in class VIII B of Bina Harapan Bangsa Middle School in Cikancung District, Bandung Regency using the experimental method. The instruments used were questionnaires with 10 statements in accordance with the indicators and accompanied by interviews with students. The conclusion of this study is the application of ice breaking in junior high school learning has a positive effect on the level of confidence of students.